An update on the management of metastatic colorectal cancer in the elderly. (October 2014) - Rosati, Gerardo; Aprile, Giuseppe; Poletto, Elena; Avallone, Antonio
SUMMARY : The availability of new chemotherapeutic and targeted agents has changed the life expectancy of patients with metastatic colorectal cancer thanks to the possibility of sequentially administering fluoropyrimidines combined with irinotecan and oxaliplatin plus monoclonal antibodies. This approach is seldom feasible in the elderly, especially because of the poor tolerability of some agents. Frail patients should only receive palliative treatment. Oppositely, fit elderly patients can be treated with more aggressive therapies, similarly to the younger ones. What is not sufficiently known is how to manage the elderly categorized as intermediate. In the coming years, it appears necessary how to accurately differentiate the elderly through a comprehensive geriatric assessment performed with validated scales and uniformed criteria simpler than those currently available.